Human Resource Transformation of Tax Auditors at the Directorate General of Taxes: an Comprehensive Review and Policy Framework Based on International Practices - Samuel Mickhael (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The quality of tax auditor human resources, encompassing competence and technological adaptation, is crucial for effective taxation; however, it is hindered by limitations in human resource autonomy and capability gaps. Objective: This study aims to synthesize global best practices in tax auditor human resource management into a coherent transformation model for the DGT. It integrates organizational structure, career development, ontology-based knowledge management, and quality-based remuneration and performance systems. Methods: A qualitative approach was employed through a comprehensive literature review. Data from scientific journals, reports, and policy documents were analyzed through theme identification, comparison, synthesis, and interpretation based on relevant theories. Results: The analysis reveals three interconnected patterns in the global literature. First, regarding organizational structure, global tax administrations consistently demonstrate a strategic tension between centralization and decentralization, which enhances local responsiveness and contextual adaptation. Second, the literature converges on the critical importance of structured capability development through academy-model institutions, competency dictionaries, and clear career paths. Third, performance management and remuneration systems exhibit a complex pattern in which motivating compensation is necessary but must be carefully designed to avoid incentive misalignment. Conclusion:Tax auditor human resource transformation requires a holistic approach: balancing centralization and decentralization, developing professional capabilities through academies and knowledge management, and designing quality- and ethics-oriented performance and remuneration systems. This study enriches the theoretical framework and offers strategic guidance for the DGT. Future research is encouraged to empirically validate this model within the DGT context.